Taxonomic review of the tribe Himalusini (Coleoptera: Staphylinidae: Aleocharinae), with new synonymies - Hashizume, Takuto; Maruyama, Munetoshi; Kishimoto, Toshio; Klimaszewski, Jan (Zootaxa, 2025)
The tribe Himalusini Klimaszewski, Pace & Center, 2010 is taxonomically reviewed based on examination of type and non-type material of its constituent genera. The species of the genus Parabrachida Cameron, 1939 are reassessed and the following new synonymy is proposed: Parabrachida decipiens Cameron, 1939 = Himalusa thailandensis Pace, Klimaszewski & Center, 2010, syn. nov. Parabrachida is transferred from the tribe Homalotini Heer, 1839 to Himalusini Klimaszewski. For the taxa included in the tribe Himalusini, one generic synonym is established: Protinodes Sharp, 1888 = Himalusa Pace, 2006, syn. nov., and one new combination is proposed: Protinodes annapurnensis (Pace, 2006), comb. nov. Notably, the present study demonstrates that Parabrachida decipiens, a species described by Cameron in 1939, was misplaced as a member of Himalusa, and its reassignment to Parabrachida based on type material highlights the critical importance of re-examining historical specimens. In total, five species in three genera are recognized in Himalusini.